Pengembangan Perangkat Pembelajaran pada Materi Asam Basa dalam Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - Sri Mardiyanti Kasim; Sudding Sudding; Tabrani Gani (Program Pasca Sarjana UNM, 2022)
This study is a development research that aims to develop learning devices on acid-base material in discovery learning model to increase students' motivation and learning outcomes that are valid, practical, and effective. The development model used in this research was the 4D development model from Thiagarajan. The learning devices that had been developed had gone through the validation phase by the validator/expert and had gone through the trial phase, resulting in learning devices that are valid, practical, and effective. The results of the study indicate that: (1) the process of developing learning devices using a 4-D model included 4 stages, namely: (a) the definition stage (define), (b) the design stage, (c) the development stage (develop), and (d) the dissemination stage, (2) the learning devices are stated to have met the validity criteria including RPP, LKPD, and THB, each of which is in very valid category.The learning devices are stated to be practical because the practicality test relates to: (a) the implementation of the device in discovery learning model has the average value M = 1.94 in the interval 1.5≤M≤2.0 with fully implemented category; (b) the teachers’ responsesare positive with a percentage of 91.75% with very practical criteria; and (c) the students' responses are very positive with a percentage of 87.65% with very practical criteria. The learning devicesare stated to be effective because it had met effective criteria with the results: (a) there are differences in the average learning motivation of students before and after the trial; (b) the learning outcomes meet the effective criteria with a class completeness percentage of 82%.